Exercise thermoregulatory responses following a 28-day sleep-high train-low regimen - Kounalakis, S. N.; Eiken, O.; Mekjavic, I. B. (European Journal of Applied Physiology, 2012)
The potentiated exercise-sweating rate observed during acute hypoxia is diminished after a sleep-high train-low (SH-TL) regimen. We tested the hypothesis that this attenuation of the sweating response after SH-TL is compensated for by an increase in heat loss via vasodilatation. Nine male subjects participated in a 28-day SH-TL regimen. Before (pre-), and after (post-) the SH-TL protocol, they performed an VO2peak test under normoxia and hypoxia. Additionally, pre- and post-SH-TL they completed three 30-min constant-work rate trials on a cycle ergometer. In one trial, the subjects inspired room air while exercising at 50 % of normoxic VO2peak (CT). In the remaining trials, subjects exercised in hypoxia (FIO2 12.5 %), either at the same absolute (HAT) or relative (50 % of hypoxic VO2peak ) work rate (HRT) as in CT. Despite similar exercise core temperature responses between pre- and post-SH-TL trials, sweating rate was potentiated in HAT pre-SH-TL [CT: 1.97 (0.42); HRT: 1.86 (0.31); HAT: 2.55 (0.53) mg/cm^2 /min; p < 0.05]. Post-SH-TL exercise sweating rate was increased for CT, and remained unchanged in HRT and HAT [CT: 2.42 (0.76); HRT: 2.01 (0.33); HAT: 2.59 (0.30) mg/cm^2min]. Pre-SH-TL, the forearm-fingertip skin temperature difference (Tskf-f) was higher in HAT than in CT and HRT by ~3.5°C (p < 0.05). The inter-condition differences in Tskf-f were diminished post-SH-TL. In conclusion, the decrease in sweating rate during hypoxic exercise, following a SH-TL regimen, was countered by an increase in vasodilatation (reduced Tskf-f), whereas SH-TL enhanced the sweating response during normoxic exercise. The mechanisms underlying these SH-TL-induced alterations in thermoregulatory responses remain to be settled.